Analisis Kebutuhan Bahan Bacaan Literasi Berorientasi Wisata Pesisir Mandangin untuk Siswa SMP sebagai Upaya Penguatan Literasi pada Era Merdeka Belajar - Afiyah Nur Kayati; Kusuma, Emy Rizta (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
PISA results show that only a few Indonesian students have a high level of reading ability. These literacy competencies can be improved through the provision of child-friendly and contextual reading materials. One of the material content that is contextual and interesting for students is tourism content. This study aims to analyze the needs of literacy reading materials for students. The method used is literature study, questionnaires, and interviews conducted to Indonesian language teachers and students. The results of this study indicate that teachers and students hope that literacy reading materials are written with very rich material, have more new vocabulary, are presented in an interesting, contextual way, can strengthen character education, and can develop students' insight into the diversity of students, especially Mandangin coastal tourism which has not been widely used. known to the Indonesian people. Literacy reading materials oriented to the Mandangin coastal tourism object can also help schools and teachers in implementing tourism-based learning.